Human Pabilloma Virus (HPV) and Cervical Cancer in Al-Najaf Governorate - Musa Nima Mezher (Journal of Global Pharma Technology, 2017)
Background: Human Papilloma virus causes benign and malignant tumours of squamous cells, many different types of HPV well known to infect a different portion of the body, also many HPV strains cause carcinoma of cervix.Objective To find the role of the virus in the cervical tumour and the extend of the effect of some tumour markers in the virus and its absence.Methods Seventy three cases of cervical cancer were obtained from Histopathological archival of central laboratory of AL-Sadder Hospital and out laboratory in Najaf AL-Ashraf Governorate. Clinical data were analysed from the medical records and formalin fixed, paraffin embedded tumour tissue were examined by Immunohistochemistry technique to the detection of the L1 protein of HPV in cervix tissue blocks. Results The expression of HPV in tissues ,women patients with cervical cancer in the present study was 69.86% (51out of 73), where strong correlation was found between expression of HPV and women patients with cervical cancer. Also found relationship between women state, residency and differential ratio between five years ago (2012-2016) in AL Najaf City. ConclusionBased on the results of the current study, Human Papilloma virus infection plays a major role in the pathogenesis of cervical cancer.Keywords: Cervical cancer, Human Papilloma virus, Human Papilloma virus L1 protein, Immunohistochemistry technique.